Association of better iron status biomarkers and coronary artery disease risk. Issue 9 (September 2014) - Zhou, Y.; Liu, T.; Kang, P.; Jia, C.
Abstract Background Epidemiological evidence concerning the role of body iron in coronary artery disease (CAD) is inconsistent, which is largely explained by the lack of relatively ideal estimations of body iron stores. Aim The aim of the present study was to attempt to explore the ideal iron indicator that has the best effect on disease risk for further studies related to iron overload metabolism research worldwide. Methods A case–control study was conducted with 258 CAD cases and 282 healthy controls. The association of serum iron (SI) parameters, including SI, total iron‐binding capacity (TIBC), serum ferritin (SF) and serum transferrin receptor (sTfR), and CAD risk, was evaluated with receiver operating characteristic analysis. The areas under the receiver operating characteristic curve (AUC) were compared with each other to indicate the one showing the strongest association with CAD risk. Results The AUC (95% confidence interval) were 0.73 (0.69–0.77), 0.74 (0.69–0.78), 0.53 (0.48–0.58) and 0.61 (0.56–0.66) for SI, TIBC, SF and sTfR respectively. After comparing the AUC with each other, the combination of SI and TIBC (AUC (95% confidence interval): 0.86 (0.83–0.90)) was superior to other examined iron parameters or the combination of iron indicators (P < 0.05). Conclusions The present study indicated that the combination of SI and TIBC may have the best effect on CAD risk. Further studies are warranted to verify this preliminary result.